Significance of BRCA2 and RB1 Co-loss in Aggressive Prostate Cancer Progression - Chakraborty, Goutam; Armenia, Joshua; Mazzu, Ying Z.; Nandakumar, Subhiksha; Stopsack, Konrad H.; Atiq, Mohammad O.; Komura, Kazumasa; Jehane, Lina; Hirani, Rahim; Chadalavada, Kalyani; Yoshikawa, Yuki; Khan, Nabeela A.; et al. (Clinical cancer research, 2020)
Previous sequencing studies revealed that alterations of genes associated with DNA damage response (DDR) are enriched in men with metastatic castration-resistant prostate cancer (mCRPC). , a DDR and cancer susceptibility gene, is frequently deleted (homozygous and heterozygous) in men with aggressive prostate cancer. Here we show that patients with prostate cancer who have lost a copy of frequently lose a copy of tumor suppressor gene ; importantly, for the first time, we demonstrate that co-loss of both genes in early prostate cancer is sufficient to induce a distinct biology that is likely associated with worse prognosis. We prospectively investigated underlying molecular mechanisms and genomic consequences of co-loss of and in prostate cancer. We used CRISPR-Cas9 and RNAi-based methods to eliminate these two genes in prostate cancer cell lines and subjected them to studies and transcriptomic analyses. We developed a 3-color FISH assay to detect genomic deletions of and in prostate cancer cells and patient-derived mCRPC organoids. In human prostate cancer cell lines (LNCaP and LAPC4), loss of leads to the castration-resistant phenotype. Co-loss of - in human prostate cancer cells induces an epithelial-to-mesenchymal transition, which is associated with invasiveness and a more aggressive disease phenotype. Importantly, PARP inhibitors attenuate cell growth in human mCRPC-derived organoids and human CRPC cells harboring single-copy loss of both genes. Our findings suggest that early identification of this aggressive form of prostate cancer offers potential for improved outcomes with early introduction of PARP inhibitor-based therapy. .